Evaluation of Liver Ischemia-Reperfusion Injury in Rabbits Using a Nanoscale Ultrasound Contrast Agent Targeting ICAM-1 - Xie, Fang (PLoS One, 2016)
OBJECTIVE: To assess the feasibility of ultrasound molecular imaging in the early diagnosis of liver ischemia-reperfusion injury (IRI) using a nanoscale contrast agent targeting anti-intracellular adhesion molecule-1 (anti-ICAM-1). METHODS: The targeted nanobubbles containing anti-ICAM-1 antibody were prepared using the avidin-biotin binding method. Human hepatic sinusoidal endothelial cells (HHSECs) were cultured at the circumstances of hypoxia/reoxygenation (H/R) and low temperature. The rabbit liver IRI model (I/R group) was established using the Pringle’s maneuver. The time-intensity curve of the liver contrast ultrasonographic images was plotted and the peak intensity, time to peak, and time of duration were calculated. RESULTS: The size of the targeted nanobubbles were 148.15 ± 39.75 nm and the concentration was 3.6–7.4 × 10(9)/ml, and bound well with the H/R HHSECs. Animal contrast enhanced ultrasound images showed that the peak intensity and time of duration of the targeted nanobubbles were significantly higher than that of common nanobubbles in the I/R group, and the peak intensity and time of duration of the targeted nanobubbles in the I/R group were also significantly higher than that in the SO group. CONCLUSION: The targeted nanobubbles have small particle size, stable characteristic, and good targeting ability, which can assess hepatic ischemia-reperfusion injury specifically, noninvasively, and quantitatively at the molecular level.